Question
\( f(x)=4 x-3 \) \( g(x)=x^{3}+2 x \) lind \( (f-8)(4) \)
Ask by Reeves Goodwin. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\((f - 8)(4) = 5\)
Solution
It looks like you want to **find** \((f - 8)(4)\). Let's break this down step by step.
Given:
- \( f(x) = 4x - 3 \)
- You're asked to find \((f - 8)(4)\), which means \( f(4) - 8 \).
**Step 1: Calculate \( f(4) \)**
\[
f(4) = 4 \times 4 - 3 = 16 - 3 = 13
\]
**Step 2: Subtract 8 from the result**
\[
(f - 8)(4) = f(4) - 8 = 13 - 8 = 5
\]
**Answer:**
\((f - 8)(4) = 5\)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Extra Insights
To solve for \( (f - 8)(4) \), we first need to determine what \( f(4) \) is. Calculating \( f(4) \): \[ f(4) = 4(4) - 3 = 16 - 3 = 13 \] Now, we subtract 8 from this result: \[ f(4) - 8 = 13 - 8 = 5 \] Therefore, \( (f - 8)(4) = 5 \).